2018
DOI: 10.1093/mnrasl/sly131
|View full text |Cite
|
Sign up to set email alerts
|

The growth and entrainment of cold gas in a hot wind

Abstract: Both absorption and emission line studies show that cold gas around galaxies is commonly outflowing at speeds of several hundred km s −1 . This observational fact poses a severe challenge to our theoretical models of galaxy evolution since most feedback mechanisms (e.g., supernovae feedback) accelerate hot gas, and the timescale it takes to accelerate a blob of cold gas via a hot wind is much larger than the time it takes to destroy the blob. We revisit this long-standing problem using three-dimensional hydrod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
296
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 287 publications
(320 citation statements)
references
References 28 publications
22
296
1
1
Order By: Relevance
“…What drives coagulation? There are at least two causes: (i) radiative cooling, which drives pressure gradients in mixed interstitial gas, the source of mass growth discussed in Gronke & Oh (2018. Cooling-induced coalescence has also been highlighted in Elphick et al (1991); Waters & Proga (2019), though merger velocities seen in those 1D (i.e., no turbulence or mixing), low overdensity (χ ∼ few) calculations are much smaller than seen there, and could not compete with breakup.…”
Section: Discussionmentioning
confidence: 99%
“…What drives coagulation? There are at least two causes: (i) radiative cooling, which drives pressure gradients in mixed interstitial gas, the source of mass growth discussed in Gronke & Oh (2018. Cooling-induced coalescence has also been highlighted in Elphick et al (1991); Waters & Proga (2019), though merger velocities seen in those 1D (i.e., no turbulence or mixing), low overdensity (χ ∼ few) calculations are much smaller than seen there, and could not compete with breakup.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cloud-scale high resolution simulations of cold clumps embedded in a hot medium with realistic conditions for the stripped tails will be fundamental to assess the hypothesis proposed in this paper and analyze the various possibilities for ISM heating (e.g. Brüggen & Scannapieco (2016); Armillotta et al (2016); Gronke & Oh (2018)).…”
Section: The Heating Ism Scenario and The Hα-x-ray Correlationmentioning
confidence: 99%
“…The other possibility is that we underestimate the ability of AGN feedback to destroy dense clumps, for example by underresolving the mixing layers at the outer clump surface (Gronke & Oh 2018), or simply due to lack of resolution to follow the fragmentation process to smaller scales. This hypothesis is supported by our high-resolution companion simulation, which showed that the fraction of dense gas that survives this particular uplifting event falls from 25 % at a resolution of ∆x min = 120 pc to 19 % at a resolution of ∆x min = 30 pc.…”
Section: Filament Lifetimesmentioning
confidence: 99%